Morphology Of The Gut Endocrine Cells In The Gastrointestinal Tract Of The Lesser Mouse Deer (Tragulus javanicus) - Srihadi Agungpriyono (Media Veteriner, 1997)
The ultrastructure of endocrine cells in the gastrointestinal tract of the lesser mouse deer (Tragulus javanicus), the smallest ruminant, was studied using electron microscopy. The cells possess components such as rough endoplasmic reticulum, golgi complexes and mitochondria and characterized prominently by the presence of cytoplasmic secretary granules. The secretary granules were polymorphous, rounded, oval or spindle shaped and varied greatly in size and electron density from one cell type to another. The granules were generally concentrated in the intranuclear region of the cells. Two types of endocrine cells could be observed. Open type cells were oval, triangular or spindle in shape, showed apical lurninal contact by means of microvilli. Closed type cells were generally round or triangular in shape. The endocrine cells were located in the basal portions, close to either capillaries or submucosal nerve fibers. The morphology of the endocrine cells was discussed in relation to their possible functions.